2013
DOI: 10.1371/journal.pone.0055798
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Invasion of Neisseria meningitidis to Host Cells Is Related to Surface Hydrophobicity, Bacterial Cell Size and Capsule

Abstract: We compared exemplar strains from two hypervirulent clonal complexes, strain NMB-CDC from ST-8/11 cc and strain MC58 from ST-32/269 cc, in host cell attachment and invasion. Strain NMB-CDC attached to and invaded host cells at a significantly greater frequency than strain MC58. Type IV pili retained the primary role for initial attachment to host cells for both isolates regardless of pilin class and glycosylation pattern. In strain MC58, the serogroup B capsule was the major inhibitory determinant affecting bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 108 publications
(160 reference statements)
2
34
0
Order By: Relevance
“…Detroit 562 cells are commonly used for N. meningitidis host cell interaction studies and exhibit high levels of bacterial adhesion (51)(52)(53). This cell line has been shown to express high levels of carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), a major Opa receptor, after exposure to cytokines or when infected with Opa-expressing N. meningitidis (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detroit 562 cells are commonly used for N. meningitidis host cell interaction studies and exhibit high levels of bacterial adhesion (51)(52)(53). This cell line has been shown to express high levels of carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), a major Opa receptor, after exposure to cytokines or when infected with Opa-expressing N. meningitidis (52).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the meningococcal wild-type strain MC58 elicited a time-dependent increase of uptake. In addition, the isogenic unencapsulated mutant showed a significantly higher rate of invasion compared to the wild-type strain due to the inhibitory effect of the serogroup B capsule polysaccharide of strain MC58 to bacterial invasion (22,23,32,51,56). We observed that meningococcal disease strain 8013/clone12 and carrier isolate ␣711 effectively adhered to Detroit 562 cells, whereas they were poorly invasive for both epithelial cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…We found that in the case of the MC58 strain the surface area is 4.98 μm . Considering MC58 as the reference strain, and assuming that only marginal differences exist in the dimensions of meningococcal strains (20), the distance between adjacent molecules on isolates expressing fHbp at levels compatible with SBA data (Table 1) ranges between 33 nm (strain M08-0240104, n = 9,390) and 115 nm (calculated average distance between two fHbp molecules) ( Table 2 and Fig. 4), whereas bacteria with negative SBA had a distance between molecules of 130 nm or more.…”
Section: The Antigen Density Required For Killing Is Consistent With C1qmentioning
confidence: 99%
“…5A). Because the capsule is much more hydrophilic than the underlying bacterial cell surface, the degree of capsulation can also be determined by measuring cellular hydrophobicity (54). We measured hydrophobicity using MATS (microbial adhesion to solvents) assays (47).…”
Section: Nmc0710 Is a Pnpase Homologmentioning
confidence: 99%